2020
DOI: 10.1097/scs.0000000000005834
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Dehydrated Human Amniotic Membrane Versus Amniotic/Chorionic Membrane Allografts to Treat Partial Thickness Facial Burns

Abstract: Background: Facial burns have significant physical and psychologic effects on patients. Human dehydrated amniotic membrane represents novel technology, yet its outcome has not been sufficiently studied to guide practice. The objective of our study is to compare the benefits of amniotic membrane (DHAM) to amniotic/chorionic membrane (DHACM) skin substitutes to treat partial thickness facial burns. Methods: Retrospective review of data collected from our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…According to Zhou et al 20 , the amniotic membrane also possesses osteoblastic properties that encourage new bone formation. Similar effects were observed in our previous study when dHACM was used as a graft material for soft tissue healing, and it also contributed to uneventful healing of the alveolar bone underneath [21][22][23] . In this study, a comparison of wound healing efficacy with and without dHACM was performed in alveoloplasty patients.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…According to Zhou et al 20 , the amniotic membrane also possesses osteoblastic properties that encourage new bone formation. Similar effects were observed in our previous study when dHACM was used as a graft material for soft tissue healing, and it also contributed to uneventful healing of the alveolar bone underneath [21][22][23] . In this study, a comparison of wound healing efficacy with and without dHACM was performed in alveoloplasty patients.…”
Section: Discussionsupporting
confidence: 84%
“…They found that the SNOSE strategy was both powerful and affordable. This technique was used in this study to reduce bias 21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation